Cambridge Checkpoint Maths-1 workbook - "Pimentel, Ric" (Hodder Education: London, 2011)
Consolidate learning with a write-in book for use in class and for homework with a parallel practice exercise for every exercise in the Student's Book.
Keywords: Mathematics-Textbook